2004
DOI: 10.1071/ar04068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impacts of deep open drains on groundwater levels in the wheatbelt of Western Australia

Abstract: Abstract. Over one million hectares of the wheatbelt of Western Australia (WA) are affected by secondary salinisation and this area is expected to increase to between 3 and 5 million hectares if current trends continue. Deep open drains, as an engineering solution to dryland salinity, have been promoted over the past few decades; however, the results of initial experiments were variable and no thorough analysis has been done. This research quantifies the effects of deep open drains on shallow and deep groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Of these, deep drains (2-3 m) are seen by farmers as the most likely solution to succeed, and it has been estimated that over 12,000 km of drains and banks have been installed (Dogramaci & Degens, 2003;Ali et al, 2004). Almost all of these drains discharge into streams and rivers and little consideration has previously been given to the ecological impacts of these discharges on already altered aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, deep drains (2-3 m) are seen by farmers as the most likely solution to succeed, and it has been estimated that over 12,000 km of drains and banks have been installed (Dogramaci & Degens, 2003;Ali et al, 2004). Almost all of these drains discharge into streams and rivers and little consideration has previously been given to the ecological impacts of these discharges on already altered aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…As is the case for many deep drains in the Wheatbelt, these have been constructed to alleviate the effects of salinity on both township infrastructure and agricultural productivity. However, many of these drains have been constructed with limited planning and design, and with little or no understanding of their effectiveness or downstream impacts (Ali et al, 2004). In the case of the Narembeen drains, their effectiveness in lowering groundwater levels has been assessed by scientists (Ali et al, 2004), but the downstream effects of these drains has not received attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The area of benefit is a measure of the drain's efficiency. It is generally expressed as the lateral extent of the drain's influence on the water table and vegetation and is dependent on soil and regolith parameters such as hydraulic conductivity (Ali et al, 2004). Previous studies at a deep drainage site at Narembeen in the Western Australian wheatbelt, reported that one year after the drain was installed, groundwater levels dropped to below 1.5 m for a distance of 200-300 m from the drain and root zone salinity decreased for a distance up to 100 m from the drain (Ali et al 2004).…”
Section: Introductionmentioning
confidence: 99%